Empowering AI: Recontextualizing Our Pedagogical Impact Through Supportive Uses of Machine Learning - Angela Gunder; Vincent Del Casino Jr; Melissa Vito; Reed Dickson (Ubiquity Proceedings, 2023)
Over time, the use of digital technologies has transformed the landscape of higher education, and the recent advancements in artificial intelligence (AI) are no exception. At the same time, there is a need to move from a binary of use versus eradication of AI systems in higher education toward critical examination and curation of the plurality of examples of how AI may lead to the empowerment of educators and students. This paper explores the potential benefits and challenges of incorporating AI into higher education while also discussing the implications for educators and students, as well as the ethical concerns surrounding the use of AI in education. The paper examines the benefits of using AI in higher education, including personalized learning, adaptive assessments, and predictive analytics, as well as emerging challenges, such as data privacy and algorithmic bias. The paper proposes a set of guiding ethical principles for the empowering use of AI in education, including transparency, collaboration, creativity, and accountability. Each author offers a call to action for educators who are required to reevaluate their relationship with technology broadly and the seismic shifts in interaction and communicative modes within a landscape forever changed by machine learning.